2018
DOI: 10.1002/pip.3061
|View full text |Cite
|
Sign up to set email alerts
|

High open‐circuit voltage CuSbS2 solar cells achieved through the formation of epitaxial growth of CdS/CuSbS2 hetero‐interface by post‐annealing treatment

Abstract: The earth‐abundant and environmentally‐friendly CuSbS2 solar cells have been struggling with low device performance, especially poor open circuit voltage (Voc). In this work, post‐annealing treatment of the CuSbS2/CdS heterojunction performed on CuSbS2‐based solar cells was firstly reported. With this treatment, we demonstrated CuSbS2 solar cells with a record Voc of 622 mV. The improvement of device performance was found peaked at 250°C post‐annealing which mainly benefits from the significantly boosted open‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 26 publications
(34 reference statements)
0
9
1
Order By: Relevance
“…The X-ray diffraction (XRD) pattern of as-deposited CuSbS 2 thin film on glass is shown in black in Figure 1a Figure S1, Supporting Information). The crystalline orientation of CuSbS 2 on glass is significantly different from our previously fabricated CuSbS 2 grown on Mo-coated glass that shows random orientation as demonstrated in Figure S2, Supporting Information, [10] which is believed to be due to different deposition substrates that exhibit various surface properties. In addition, we have also identified small amount of Sb 2 S 3 secondary phases as marked by asterisk in Figure 1a.…”
contrasting
confidence: 62%
“…The X-ray diffraction (XRD) pattern of as-deposited CuSbS 2 thin film on glass is shown in black in Figure 1a Figure S1, Supporting Information). The crystalline orientation of CuSbS 2 on glass is significantly different from our previously fabricated CuSbS 2 grown on Mo-coated glass that shows random orientation as demonstrated in Figure S2, Supporting Information, [10] which is believed to be due to different deposition substrates that exhibit various surface properties. In addition, we have also identified small amount of Sb 2 S 3 secondary phases as marked by asterisk in Figure 1a.…”
contrasting
confidence: 62%
“…Heat treatment (HT) is a common strategy for surface and interface engineering in heterojunction structures, which has been widely used to promote grain growth, [ 34 ] improve the crystallinity, [ 35 ] and passivate the interface defects. [ 36 ] Recently, Yan et al. demonstrated that by HT processing of CZTS/CdS, significant efficiency enhancement was achieved in CdS‐buffer based CZTS solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The certified highest power conversion efficiencies (PCE) of 12.6%, 12.5% and 11.0% have been achieved by using CZTSSe, CZTSe, CZTS absorber, respectively [1][2][3]14]. Note that the PCE of kesterite so far dominates all emerging inorganic thin-film PV technologies, highlighting its potential for cost-effective solar cell applications [15][16][17][18][19][20][21][22]. Nevertheless, the present record PCE of CZTSSe is still lower than the physical limit defined by the Shockley-Queisser (S-Q) theory or first-principles calculations [23][24][25].…”
mentioning
confidence: 99%